Effect of Red Y2O3:Eu3+ phosphor on the color quality and luminous efficacy of the 7000K IPW-LEDs - Van-Duc Phan; Minh Tran; Le Anh Vu; Hoang-Nam Nguyen; Tran Thanh Trang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this study, we investigate the effect of concentration of the red Y2O3:Eu3+ phosphor on the Color Rendering Index (CRI), Color Quality Scale (CQS) and Lumen Output (LO) of the 7000K in-cup packaging white LEDs (IPW-LEDs). The physical model of the 7000K IPW-LEDs is conducted by Light Tools software. By varying the concentration of the red phosphor from 0% to 0.36%, we use the Light Tools software to investigate the CRI, CQS, and LO of the 7000K IPW-LEDs. From the research results, it can be observed that the CRI and CQS can be increased to 85 and 71, respectively. However, the LO has a decrease in the increasing trend of the red phosphor concentration. This paper provides the new recommendation for the manufacturing of the IPW-LEDs.